Ontogenetic variations and structural adjustments in mammals evolving prolonged to continuous dental growth - Gomes Rodrigues, Helder (R Soc Open Sci, 2017)
Studying dental ontogeny in mammals can provide valuable insight on the evolution of their masticatory apparatus and their related adaptations. The multiple acquisitions of a prolonged to continuous growth of teeth in herbivorous mammals in response to high abrasion represent an intensively investigated issue. However, the ontogenetic and architectural patterns associated with these repeated dental innovations remain poorly known. Here, we focused on two case studies corresponding to distant mammalian clades, the extinct Mesotheriidae (Notoungulata), which shared some striking dental features with the extant Ctenodactylidae (Rodentia). We studied the impact of prolonged to continuous growth of molars on their occlusal complexity, their relative size and their dynamics in the jaw. We found that variations of occlusal complexity patterns are the result of paedomorphic or peramorphic heterochronic processes impacting dental crown. We showed that variations in both upper and lower molar proportions generally follow the inhibitory developmental cascade model. In that context, prolonged dental growth implies transitory adjustments due to wear, and also involves dental migration and loss when combined with molar lengthening. Interestingly, these features may be present in many mammals having prolonged dental growth, and emphasize the crucial need of considering these aspects in future evolutionary and developmental studies.